1992
DOI: 10.1038/bjc.1992.95
|View full text |Cite
|
Sign up to set email alerts
|

Levels of expression of the mdr1 gene and glutathione S-transferase genes 2 and 3 and response to chemotherapy in multiple myeloma

Abstract: Summary We have quantitated the levels of mRNAs in bone marrow samples from patients with multiple myeloma of the mdrl gene (responsible for the Multidrug Resistance phenotype) and for two of the glutathione S-transferase gene. GST-2 and GST-3 (which can also inactivate a wide variety of cytotoxic drugs) and examined the relationship between the levels of expression of these genes and response to subsequent chemotherapy. From a total of 47 patients. 37 were treated with chemotherapy with 34 evaluable for respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 20 publications
2
26
0
1
Order By: Relevance
“…Melphalan, included in this category, is one of the most frequently used chemotherapeutic agents in the initial treatment of MM. The mRNA levels for the genes GST-2 and mdr1 significantly correlate in MM, supporting the theory that resistant tumors have several concurrent mechanisms of chemoresistance (7).…”
supporting
confidence: 57%
“…Melphalan, included in this category, is one of the most frequently used chemotherapeutic agents in the initial treatment of MM. The mRNA levels for the genes GST-2 and mdr1 significantly correlate in MM, supporting the theory that resistant tumors have several concurrent mechanisms of chemoresistance (7).…”
supporting
confidence: 57%
“…Although patients with MM at presentation have a low percentage of tumor cells that express MDR1 protein, this percentage increases up to 50% in patients after chemotherapy (27,28). These findings suggest that efforts should focus on overcoming some of the problems associated with paclitaxel-based therapy, including issues with formulation, administration, and susceptibility to resistance conferred by the drug-efflux protein P-glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was shown that overexpression of P-gp is responsible for the resistance to a new second generation proteasome inhibitor, carflizomib (Hawley et al, 2013). MRP1 overexpression generally was not detected in MM cells (Lynsenmeyer et al, 1992;Marie, 2001). LRP expression was detected in approximately half of MM patients and is associated with a poor response to melphalan-based induction chemotherapy (Lokhorts et al, 1996).…”
Section: Differential Expression Levels Of Abc Transporter Protein Famentioning
confidence: 99%